2005
DOI: 10.1890/04-1162
|View full text |Cite
|
Sign up to set email alerts
|

Duck Nest Survival in the Missouri Coteau of North Dakota: Landscape Effects at Multiple Spatial Scales

Abstract: Nest survival is one of the most important parameters in the population dynamics of grassland‐nesting ducks (Anas and Aythya spp.) that breed in the Prairie Pothole Region of North America. Grassland habitats used by these species are increasingly threatened by habitat loss and the coincident fragmentation, which may indirectly alter nest survival through effects on predators. Although predators are the dominant cause of nest loss, they are difficult to monitor directly. Thus, indirect analyses of habitat vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(215 citation statements)
references
References 48 publications
13
199
1
2
Order By: Relevance
“…Within this landscape, nest-site placement by female sage-grouse was influenced by landscape variables at multiple spatial scales (Dzialak et al 2011a); however, DSR of nests was most influenced by nest site-specific variables (area ≤ 30 × 30 m), similar to another study by Manzer and Hannon (2005). This finding is in contrast to other studies which found that landscape-level variables were most influential on the success of nests by ground-nesting birds (Stephens et al 2005;Moynahan et al 2007). Examining the variables that were included in the final model revealed potential mechanisms (i.e., visual and olfactory) that predators used to locate nests when considering that nest depredation and direct predation of the incubating female were the most common sources of nest failure.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Within this landscape, nest-site placement by female sage-grouse was influenced by landscape variables at multiple spatial scales (Dzialak et al 2011a); however, DSR of nests was most influenced by nest site-specific variables (area ≤ 30 × 30 m), similar to another study by Manzer and Hannon (2005). This finding is in contrast to other studies which found that landscape-level variables were most influential on the success of nests by ground-nesting birds (Stephens et al 2005;Moynahan et al 2007). Examining the variables that were included in the final model revealed potential mechanisms (i.e., visual and olfactory) that predators used to locate nests when considering that nest depredation and direct predation of the incubating female were the most common sources of nest failure.…”
Section: Discussionsupporting
confidence: 46%
“…Processes on the landscape occur and interact at multiple spatial scales (Wiens 1989), and likely carry-over to influence predator behavior on the landscape because most predators also perceive the landscape at various spatial scales (Chalfoun et al 2002;Stephens et al 2005). For these reasons, we use a multi-scalar approach to examine the relationships between DSR of nests and spatial landscape features (i.e., anthropogenic and landscape features, and topography) important to sagegrouse during nesting.…”
Section: Spatial Variables: Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…I included a seasonal trend variable to explain temporal variation in the nesting season, with earlier nests predicted to be more successful than later nests. I also included a model with nest age to allow nest survival to vary during laying and incubation (Klett and Johnson 1982, Stephens et al 2005, Grant and Shaffer 2012. I included a model with annual variability, where year was modeled as a categorical variable.…”
Section: Interactionsmentioning
confidence: 99%